Development of Multimedia Packages for the Promotion of Teaching Morality and Positive Values to Youths in Four Regions - Duangchant, Shatchaya; Piromnok, Narongrit; Chunhapataragul, Thinnagorn (ASEAN Journal of Education, 2018)
The development of multimedia packages to promote the teaching of morality and positive values to youth in four regions was divided according to the local dialects of Thailand, namely Northern Thai, Central Thai, Northeastern Thai and Southern Thai. The objectives of the research were: (1) to study the body of knowledge that is appropriate for use in the creation of multimedia learning packages to promote the moral values of youth in the four regions, (2) to develop multimedia learning packages to promote the moral values of youths in the four regions, and (3) to study the level of satisfaction that the youths have with regard to the multimedia learning packages after they were improved. The methodology of the research was conducted by gathering experiences and real situations from regional Thai cultures to be presented in storyboard form. The relationships between the content and the regions were verified by sociology experts before the multimedia were produced in order to educate children with participative information and to impart values, so they can take part in society and prepare to be part of the future national strength and resources with positive values. The research results found that the outcome from the study of the body of knowledge provided the content of the stories for the creation of the multimedia learning packages. A total of 40 stories, in accordance with the headings listing the 10 duties found in the song “The Child’s Duties”, resulted from the development of multimedia learning packages consisting of 2-dimensional multimedia using the Central Thai dialect for a total of 10 parts and short films for a total of 40 parts (divided according to local dialects with 10 parts per region) for youths in Thailand. The results of the investigation into the level of satisfaction found that the sample group from the Central Thai dialect group had satisfaction with the multimedia learning high levels of satisfaction with the multimedia learning packages that had been improved, namely the Northeastern Thai dialect, Northern Thai dialect and Southern Thai dialect groups, respectively, with the sample groups of all four regions in agreement that the improved learning packages are easy to understand as well as enjoyable and attractive, and that the use of local dialects is able to effectively convey the ideas related to behavior that can be applied to use in daily life.